Propranolol inhibits cell viability and expression of the pro-tumorigenic proteins Akt, NF-ĸB, and VEGF in oral squamous cell carcinoma - Shibuya, Caroline Miho [UNESP]; Tjioe, Kellen Cristine [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Bernabé, Daniel Galera [UNESP] (Elsevier, 2022)
Background: Propranolol (PPL) has been suggested as an option for the treatment of various types of cancer. However, data regarding its effectiveness against oral cancer are scarce. Thus, we aimed to evaluate the antitumor potential of PPL in oral squamous cell carcinoma (OSCC) in vitro. Methods: OSCC cell lines, SCC-9, SCC-25, and Cal27, were treated with PPL at different times and concentrations. OSCC cells were treated with PPL alone or in combination with cisplatin (CDDP) or 5-fluorouracil (5-FU). Cell viability was determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The expression of phosphorylated (p)-Akt, p-S6, p-PTEN, p-P65, and VEGF was verified by immunofluorescence. The migratory activity of OSCC cells was evaluated using a wound-healing assay. Results: PPL reduced OSCC cell viability in a dose- and time-dependent manner. Concentrations above 300 µM, 110 µM, and 100 µM for SCC-9, Cal27, and SCC-25, respectively, significantly eliminated tumor cells. The combination of PPL with CDDP and 5-FU enhanced their antitumor effects. There was a modest difference between the use of the IC30 and IC50 of PPL in the combinatory options. PPL downregulated p-P65 NF-ĸB and VEGF expression in SCC-9 and Cal27 cells but not in SCC-25 cells. PPL inhibited the phosphorylation of Akt and s6 and increased the phosphorylation of PTEN in all OSCC cell lines studied. PPL inhibited OSCC cell migration after 24 h of treatment. Conclusion: PPL was effective against oral cancer cells and enhanced standard-of-care. PPL inhibited cell viability and the expression of pAkt, NF-ĸB, and VEGF.
Keywords: beta-adrenergic receptor; Beta-blockers; Distress; head and neck cancer; Head and neck squamous cell carcinoma; NF-kB; Norepinephrine; oral cancer; oral neoplasms; oral squamous cell carcinoma; Propranolol